A Clinical and Laboratory Profile of Multiple Myeloma - Chowdhury, Md Rezaul Karim (Journal of Enam Medical College, 2018)
Background: Myeloma, the most common malignant disease of bone, is incurable and occurring with increasing frequency in elderly population. Typical clinical features are weakness, fatigability, bone pain, anemia, renal insufficiency and hypercalcemia. Incidental discovery on comprehensive laboratory panels is common. Serum or urine protein electrophoresis or immunofixation and bone marrow aspirate analysis help the diagnosis of multiple myeloma. Objective: The aim of this study was to define and evaluate the clinico-laboratory features of newly diagnosed adult multiple myeloma (MM) patients in the context of Bangladesh. Materials and Methods: This study was carried out in two centers, from October 2005 to January 2010 in Bangabandhu Sheikh Mujib Medical University (BSMMU) and July 2012 to June 2017 in Enam Medical College and Hospital (EMCH). Thirty two diagnosed valid cases of multiple myeloma were included in this study. Clinical history, physical and relevant laboratory findings were carefully recorded and analyzed. Results: In this study among 32 patients, 29 were males and 3 were females with mean age 51.94 ± 10.09 years. The common complaints were bone pain, weakness and fatigue. The common clinical findings were bone tenderness, pallor and high ESR (ESR of all the study patients was more than 100 mm in 1st hour). Hemoglobin level was <8.5 gm/dL in 13 patients, serum creatinine ≥2 mg/dL in seven patients, serum albumin <30 mg/L in 14 patients and serum β2 microglobulin >5.5 mg/L in 15 patients. Three patients were hypercalcemic. Lytic lesions were the most common radiological finding in the study. Conclusion: This study showed that multiple myeloma is a disease of the middle and elderly aged population with male preponderance, with high male female ratio. Multivenued studies are needed to view the real picture of multiple myeloma in the context of Bangladesh. J Enam Med Col 2018; 8(3): 159-164